Evidence on types of interventions for the institutionalization of pharmaceutical care: integrative review (Research, Society and Development, 2022)
Introduction: Pharmaceutical assistance is a set of actions aimed at the promotion, protection, and recovery of health, both individual and collective, having the drug as an essential input and aiming at access and its rational use. Objective: To synthesize evidence on intervention strategies in the context of the institutionalization of pharmaceutical care in Brazil. Methodology: Integrative review. Results: 16,356 records were retrieved: 11 from Health Evidence, 43 from Epistemonikos, 01 from Cochrane, 20 from Health Systems Evidence, 4,369 from the Virtual Health Library and 11,700 from Google Scholar. 19 articles were selected: 15 cross-sectional studies, 02 literature reviews and 02 case studies. Conclusion: Educational, organizational, sectoral, financial, and regulatory policy interventions are recognized to improve clinical, humanistic, and economic outcomes in the field of institutionalization of pharmaceutical assistance.